Heterogeneous analysis of pollution abatement via renewable and nonrenewable energy: Lessons from investment in G20 nations - Kazeem Bello Ajide; Peter Ekundayo Mesagan (African Governance and Development Institute (AGDI), 2022)
Environmental sustainability and climatic change mitigation seem central in the fight against global warming and continuous human sustenance in the 21st century. However, non-renewable and renewable consumption energies lie at the core of these pollution concerns, particularly among the G20 economies that are top pollution emitters in the world. Unlike other mediators in energy-pollution nexus, capital investment has been argued to ameliorate or amplify the relationship. To this end, the study specifically sets out to unravel the mediating role of capital investment in energy-pollution link together with other pollution confounders including trade openness, foreign direct investment and energy use for G20 economies over the period 1990- 2017. Using the pooled mean group estimator, the study accounts for both cross-sectional dependence and heterogeneity among the countries. They key findings show that renewable energy to negatively impact carbon emissions in both the short- and long-run, while nonrenewable energy positively having a reverse impact. In addition, the results show that capital investment as lowering pollution in the short-run but increases it in the long-run. Lastly, on interacting capital investment with renewable energy, pollution is found to reduce to pollution in both short- and long-run, while its interaction with non-renewable energy expands pollution in both short- and long-run. On the policy front, since capital investment provides an important channel to reduce pollution in G20 nations, it is therefore recommended that if energy consumption is to work through the capital investment channel to lower pollution in the G20, the proportion of renewable energy must increase relative to non-renewable energy in their energy mix.
Keywords: Q41; Q42; Q53; F23; O50; 330; Capital Investment; Renewable Energy; Non-renewable Energy; Carbon Emissions